Ventral fixation in atlantoaxial instability with axial fracture in a dog - Ozak, A.; Besalti, O.; Pekcan, Z.; Eminaga, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
This study reports the diagnosis and the surgical management of atlanto-axial instability with an oblique axial fracture in a dog. The fracture was diagnosed by radiography and Computed Tomography (CT). In the CT views, the appearance of the distortion of the atlantoaxial articular surface was interpreted as instability. The stabilization was achieved with the cancellous screws. Following the surgery, the neurological status improved and the dog no longer had marked neurological deficits.
Keywords: Atlantoaxial instability; ventral fusion; axial fracture; dog